Contribuições para o desenvolvimento de um método mecanístico-empírico de dimensionamento de pavimentos asfálticos - Santiago, Lucimar da Silva (2017)
The asphalt pavement design guide officially followed by the Brazilian National Department of Transport Infrastructure – DNIT is obsolete if compared to other advanced pavement design guides around the world. Firstly, that design does not take into account relevant aspects regarding pavement behavior, such as traffic, load-supporting capacity, and weather conditions. In addition, it does not consider the prediction of pavement life performance regarding the recurrent distresses observed in Brazil, such as fatigue and permanent deformation. However, a mechanistic-empirical method based on field data developed by Rede Temática de Asfalto has brought technical and scientific advances in order to change the current scenario. The referred method is meant to be applied in three levels of analysis: basic, intermediate and advanced. The basic level is already in progress. Thus, the present research contributes to the intermediate level by developing a new design method associated with an equation to forecast the percentage of cracked area. To attain such goal, it was assessed the fatigue damage evolution data obtained from the analysis of asphaltic material deformation results by using the Simplified Viscoelastic Continuum Damage (S-VECD) model, associated to an elastic-linear structural analysis. The findings were promising and made possible the development of a satisfactory transfer function of the correlation between the percentage of cracked areas measured in the field and the ones predicted through the model. Considering the due limitations, the developed transfer function had been inserted in the proposed method, through the computer program CAP 3D-D.